'We Came To Realize We Are Judges': Moral Careers of Elected Lay Jurists in Rwanda's Gacaca Courts. (24th October 2020) - Nyseth Brehm, Hollie; Roberts, Louisa L; Uggen, Christopher; Gasanabo, Jean-Damascene
Abstract: In the wake of the 1994 genocide, Rwanda's government created the Gacaca courts to hold suspected perpetrators accountable. Although much has been written about these courts, researchers know comparatively less about the 250, 000 individuals who served as Gacaca court judges ( inyangamugayo ). We draw upon 135 interviews to explore how the inyangamugayo entered and adapted to their new public roles as moral arbiters, how these judges understood Gacaca 's missions, and how their social identities evolved over the course of multiple status transitions. Building on Erving Goffman's sequential approach to moral careers, we trace the process of becoming a judge. In doing so, we highlight the two overarching missions that surfaced during the interviews – justice and reconciliation – and how the judges continued to view themselves as inyangamugayo even after the courts closed.